A Case of Localized Prostate Cancer Associated with Polymyalgia Rheumatica with Marked Symptomatic Improvement after Robot-Assisted Radical Prostatectomy. (15th October 2021) - Kawase, Makoto; Nakane, Keita; Namiki, Sanae; Takeuchi, Yasumichi; Ueda, Shota; Kawase, Kota; Nakai, Chie; Takeuchi, Shinichi; Kato, Daiki; Takai, Manabu; Iinuma, Koji; Fuwa, Masayuki; et al.
Abstract : A 73-year-old man visited our hospital with chief complaints of fever of unknown origin and bilateral shoulder and hip joint pain. He was initially diagnosed with polymyalgia rheumatica (PMR). Although the patient was treated with prednisolone 15 mg/day, his PMR-related symptoms did not improve. Further examination was performed as the patient was suspected of having paraneoplastic syndrome. Assessment results showed prostate cancer without metastases. After undergoing robot-assisted radical prostatectomy, the patient's PMR-related symptoms dramatically improved. Hence, the prednisolone dose was decreased to 4 mg/day. PCa may have triggered the development of PMR through the activation of immune-mediated systemic inflammatory responses.